Advances in Reconfigurable Mechanisms and Robots II - Ding, Xilun; Kong, Xianwen; Dai, Jian S. (Mechanisms and Machine Science, 2016)
This book presents the most recent advances in the research and applications of reconfigurable mechanisms and robots. It collects 93 independently reviewed papers presented at the Third ASME/IFToMM International Conference on Reconfigurable Mechanisms and Robots (ReMAR 2015) held in Beijing, China, 20-22 July 2015. The conference papers are organized into seven parts to cover the reconfiguration theory, topology, kinematics and design of reconfigurable mechanisms including reconfigurable parallel mechanisms. The most recent results on reconfigurable robots are presented including their analysis, design, simulation and control. Bio-inspired mechanisms are also explored in the challenging fields of rehabilitation and minimally invasive surgery. This book further addresses deployable mechanisms and origami-inspired mechanisms and showcases a wide range of successful applications of reconfigurable mechanisms and robots. Advances in Reconfigurable Mechanisms and Robots II should be of interest for researchers, engineers and postgraduate students in mechanical engineering, electrical engineering, computer science and mathematics. .